A three‐dimensional ZnII coordination polymer constructed from 1, 1′‐biphenyl‐2, 2′, 4, 4′‐tetracarboxylate and 1, 4‐bis(1H‐imidazol‐1‐yl)benzene ligands exhibiting photoluminescence. Issue 2 (12th January 2017) - Su, Feng; Lu, Liping; Zhou, Chengyong; Wang, Xiaoxia; Sun, Long; Han, Chun
Abstract : In a three‐dimensional framework containing [Zn2 (CO2 )] n chains in which carboxylate groups bridge tetrahedral Zn II cations in a syn – anti mode, the chains are crosslinked by 1, 1′‐biphenyl‐2, 2′, 4, 4′‐tetracarboxylate and 1, 4‐bis(1 H ‐imidazol‐1‐yl)benzene ligands. Abstract : Ligands based on polycarboxylic acids are excellent building blocks for the construction of coordination polymers; they may bind to a variety of metal ions and form clusters, as well as extended chain or network structures. Among these building blocks, biphenyltetracarboxylic acids (H4 bpta) with C 2 symmetry have recently attracted attention because of their variable bridging and multidentate chelating modes. The new luminescent three‐dimensional coordination polymer poly[(μ5 ‐1, 1′‐biphenyl‐2, 2′, 4, 4′‐tetracarboxylato)bis[μ2 ‐1, 4‐bis(1 H ‐imidazol‐1‐yl)benzene]dizinc(II)], [Zn2 (C16 H6 O8 )(C12 H10 N4 )] n, was synthesized solvothermally and characterized by single‐crystal X‐ray diffraction, elemental analysis and IR spectroscopy. The crystal structure contains two crystallographically independent Zn II cations. Both metal cations are located on twofold axes and display distorted tetrahedral coordination geometries. Neighbouring Zn II centres are bridged by carboxylate groups in the syn – anti mode to form one‐dimensional chains. Adjacent chains are linked through 1, 1′‐biphenyl‐2, 2′, 4, 4′‐tetracarboxylate and 1, 4‐bis(1 H ‐imidazol‐1‐yl)benzene ligands to form a three‐dimensional network. In the solid state, the compound exhibits blue photoluminescence and represents a promising candidate for a thermally stable and solvent‐resistant blue fluorescent material.